Studying the Quantity and Composition of Traffic in Public Transport Directions - Mizrabov Ulug‘bek Boliqul o‘g‘li (Genius Journals, 2023)
Conducted on the main streets of Jizzakh, which are a mixture of cars and public transport on the main streets of Jizzakh, show that the intensity of traffic on these streets depends on the importance of the road, traffic .. it can be seen that they differ from each other depending on a number of factors such as composition, condition, and so on. The influence of changes in the volume and composition of traffic on changes in the speed of movement and the number of traffic accidents is analyzed.
Keywords: road network; bus; minibus; traffic accident